Pre‐analytical and analytical aspects of EDTA‐plasma iron measurement. Issue 10 (21st December 2015) - Leuenberger, Nicolas; Baume, Norbert; Robinson, Neil; Saugy, Martial
Abstract : It has been demonstrated that quantification of ethylenediaminetetraacetic acid (EDTA)‐plasma iron could complement the already existing Athlete Biological Passport (ABP) variables and provide additional evidence for blood transfusion. Here, a fast preparation of a blood sample was proposed directly in the EDTA‐blood tube without performing an aliquoting step. In addition, correlations in paired serum and EDTA‐plasma samples and storage stability were investigated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract :